Interaction of profitability and capital intensity in determining corporate tax aggressiveness - Ardianti, Putu Novia Hapsari; Mahaputra, I Nyoman Kusuma Adnyana; Yaswari, Ida Ayu Made Adinda (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
Tax aggressiveness reflects a company's strategy to minimize tax obligations through tax planning. This study aims to examine the influence of liquidity, leverage, profitability, firm size, and capital intensity on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. Using purposive sampling, 72 companies were selected, resulting in 216 observational data points. The analysis method employed is multiple linear regression. The results show that profitability has a significant positive effect on tax aggressiveness, while capital intensity has a significant negative effect. These findings suggest that companies with higher profitability tend to be more aggressive in their tax planning, while those with higher capital intensity may adopt more conservative tax strategies. This study provides insights for policymakers to enhance the effectiveness of tax regulations and assists companies in understanding internal factors affecting their tax policies, offering guidance for future decision-making.